Perceived parental alcohol problems, internalizing problems and impaired parent — child relationships among 71 988 young people in Denmark. (29th July 2016) - Pisinger, Veronica S. C.; Bloomfield, Kim; Tolstrup, Janne S.
Abstract: Aims: To test the hypothesis that young people with perceived parental alcohol problems have poorer parent–child relationships and more emotional symptoms, low self‐esteem, loneliness and depression than young people without perceived parental alcohol problems. Design: Cross‐sectional analysis using data from the Danish National Youth Study 2014, a web‐based national survey. Setting: Denmark. Participants: A total of 71.988 high school and vocational school students (aged 12–25, nested in 119 schools and 3.186 school classes) recruited throughout 2014. Measurements: Outcome variables included internalizing problems such as emotional symptoms, depression, self‐esteem, loneliness and aspects of the parent–child relationship. The main predictor variable was perceived parental alcohol problems, including the severity of the perceived problems and living with a parent with alcohol problems. Control variables included age, sex, education, ethnicity, parents' separation and economic problems in the family. Findings: Boys and girls with perceived parental alcohol problems had statistically significant higher odds of reporting internalizing problems (e.g. frequent emotional symptoms: odds ratio (OR)= 1.58 for boys; 1.49 for girls) and poor parent–child relationships (e.g. lack of parental interest: OR = 1.92 for boys; 2.33 for girls) compared with young people without perceived parental alcohol problems. The associations were not significantly stronger for mother's alcohol problems or if the young person lived with the parent with perceived alcohol problems. Conclusion: Boys and girls in secondary education in Denmark who report perceived parental alcohol problems have significantly higher odds of internalizing problems and poorer parent–child relationships compared with young people without perceived parental alcohol problems.